Patrimônio Cultural Edificado Cearense: a contribuição de Domingos Linheiro - Oliveira, Beatriz Chaves (2024)
This research has as its object of study part of the work of architect Domingos Linheiro in Ceará. His professional career is marked by restoration interventions and reuse of Ceará's historical heritage in buildings and urban sites. We seek to understand how it works with the dialogue between new and pre-existing elements in these spaces that are intended to safeguard and extend the useful life of listed assets. The dissertation is divided into three chapters. Chapter 1-Theories of architectural restoration deals in general with the theoretical framework that underpins the interventions. Chapter 2-The professional training of architect Domingos Linheiro deals with the paths that led him to projects and works with this theme. It allows you to learn about your academic training, your proximity to freehand drawing, your courses, your studies, your teaching practice, your practice as a manager and other contacts that were essential in your specialization in architectural restoration. Chapter 3 - Restoration works by architect Domingos Linheiro presents restoration works carried out by the architect's interventions. Part of his production is covered by choosing works that are very significant for Ceará's architecture: Church of Nossa Senhora da Conceição de Almofala (Itarema)-1983, Passeio Público (Fortaleza)-1994, Museu da Indústria (Fortaleza)-2005 , Mother Church of N. Sra. da Assunção (Viçosa do Ceará)-2006, Sobrado Dr. José Lourenço (Fortaleza)-2007 and the Municipal Palace (Fortaleza)-2009. With these works, an analysis is made of the reflection of his theoretical assumptions and his position regarding the practice of restoration in his professional career as an architect. Although it is known that in the architectural production of Ceará, Domingos Linheiro is certainly the architect who created the most restoration projects, the writing of this part of the history of Ceará's architecture is still unsaid.